État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Care Trajectories for Yukon Francophone Seniors - De Moissac, Danielle (Parteneriat communauté en santé, 2023)
Over the past several years, the Yukon Government has been exploring the matter of aging in place for its senior citizens (Government of Yukon, 2019). In the 2018 report entitled Yukon Health Status Report – Focus on Seniors, the Government of Yukon (2018) presented a profile of the health and well-being of Yukon seniors. t is important to note, however, that the voice of Francophone seniors is neither represented in the Focus on Seniors report (Government of Yukon, 2018) nor in the public engagement documentation, except for the mention of a liaison service for Francophones when discharged from the hospital (Government of Yukon, 2018 What we Heard About Aging in Place., p. 26). Although Francophones were able to participate in the engagement process, no mention was made about any specific needs of Francophone seniors. In light of the fact that Francophone seniors living in a minority language situation are aging at a proportionally faster rate than the overall Canadian population (Bouchard et al., 2015) and that this results in increased use of home care and other services (Van Kemenade, Bouchard & Bergeron, 2015), the needs of seniors from both of Yukon’s official language groups must be considered. This report provides information to further our understanding of this matter. Report Objectives: 1) To present findings related to Yukon Francophone senior care trajectories, from the moment when they first perceive the need for support with their overall health, on the physical as well as the mental and social levels. 2) To identify the care, health, and social service needs of these seniors, according to the services available, such that the active offer of French language services meets their needs.
Nombre de pages: 22

Trajectoires de soins pour les aîné(e)es francophones du Yukon - de Moissac, Danielle (Partenariat communauté en santé, 2023)
Le gouvernement du Yukon s’intéresse depuis quelques années à la question du vieillissement chez soi pour sa population aînée (gouvernement du Yukon, 2019). Un rapport publié en 2018 intitulé Yukon Health Status Report: Focus on Seniors (Gouvernement du Yukon, 2018) présente le profil de santé et de mieux-être des aîné·e·s du territoire. Force est de constater, toutefois, que la voix des francophones n’est représentée ni dans le rapport sur la santé des aîné·e·s (Gouvernement du Yukon, 2018) ni dans les écrits émanant des consultations, autrement que par la mention d’un service de liaison pour les francophones à leur congé de l’hôpital (p. 26, Gouvernement du Yukon, 2018 What we Heard About Aging in Place.). Bien que des francophones aient pu participer aux consultations, aucune trace des besoins spécifiques des aîné·e·s de la francophonie n’est rapportée. Sachant que la population aînée francophone vivant en situation linguistique minoritaire vieillit proportionnellement plus rapidement que l’ensemble de la population canadienne (Bouchard et coll., 2015) et que cela engendre une utilisation accrue de soins à domicile et d’autres services (van Kemenade, Bouchard et Bergeron, 2015), il est important de saisir les besoins des personnes âgées issues des deux groupes de langues officielles du Yukon. Ce présent rapport pourra mieux nous informer à cet égard. Objectifs du rapport: 1) Exposer les constats relatifs aux trajectoires de soins pour les aîné·e·s francophones du Yukon, à partir du moment où ils ressentent le besoin de soutien en lien avec leur santé globale, tant physique que mentale et sociale; 2) Prendre connaissance des besoins de ces aîné·e·s quant aux soins et services sociaux et de santé, en relation avec les services disponibles dans une optique d’offre active de services en français qui répondent à leurs besoins.
Nombre de pages: 22

Being small and outnumbered: Service and sociocultural exclusion among older linguistic minorities in Finland - Nyqvist, Fredica; Björklund, Siv; Lindell, Marina; Nygård, Mikael (Linguistic Minorities and Society, 2021)
Our study aims to analyze the social exclusion of older Swedish and Finnish speakers living as linguistic minorities in bilingual municipalities in Finland, where municipal authorities are required to offer services in both languages. Data was taken from the 2016 Language Barometer Survey, measuring the quality of language services in bilingual municipalities (n=33). For the purposes of our study, we focused on 2,030 people between the ages of 60 and 84. We included four different language groups, unilingual Swedish and Finnish speakers and Finnish-Swedish bilinguals and examined two social exclusion domains: service and sociocultural exclusion. The results showed that living as a regional minority poses a greater challenge when it comes to social inclusion for the unilingual and bilingual Swedish minority, as opposed to the Finnish-speaking minority. We conclude that linguistic rights seem to be achieved in the most egalitarian way in bilingual municipalities where Swedish is the majority language. Keywords: older adults, linguistic minority, bilingual, social exclusion, Finland

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Le renforcement des capacités : déclin ou levier à l'amélioration de la qualité de vie des aînés ? Le cas de St-Wilfred et de Robertville en Acadie - Simard, Majella (Reflets, 2022)
Le vieillissement de la population représente une réalité complexe. Bien que les causes attribuables à ce phénomène fassent consensus auprès des chercheurs, ses manifestations et ses conséquences diffèrent d’un endroit à l’autre. Dès lors, le rythme et l’intensité du vieillissement ainsi que les moyens déployés par les différents acteurs sociaux pour en atténuer les effets et améliorer les conditions de vie des aînés se manifestent aussi différemment selon les milieux géographiques. Pour diverses raisons liées à la démographie et à la géographie, les défis liés à la gestion du vieillissement tendent à se manifester avec plus d’acuité en milieu minoritaire francophone. L’objectif de cet article consiste à examiner la contribution du modèle de renforcement des capacités à l’amélioration de la qualité de vie des aînés vivant au sein de deux localités sises en milieu rural minoritaire francophone. L’étude de cas exploratoire couplée à l’approche des représentations sociales des acteurs a été retenue comme méthode d’analyse. Des entrevues semi-dirigées effectuées auprès d’intervenants locaux et communautaires ainsi que la tenue de deux groupes de discussion constituent les instruments d’analyse qui ont été mobilisés. Bien que les résultats de notre analyse révèlent le rôle d’avant-plan de la résilience, du réseautage, de la vie relationnelle, du sentiment identitaire et du capital social dans l’amélioration de la qualité de vie des aînés, ces composantes relatives à leurs facultés s’avéreraient insuffisantes afin de favoriser un vieillissement sur place, d’où la nécessité de déployer en amont une politique territoriale du vieillissement. Mots-clés : vieillissement, milieu rural, renforcement des capacités, qualité de vie, Acadie